Enfortumab Vedotin in metastatic bladder cancer: a case report of durable clinical efficacy in a pretreated patient - Passalacqua, Maria Ilenia; Squeri, Andrea; Sciumè, Calogero; Ieni, Antonio; Santarpia, Mariacarmela (Acta Biomedica Atenei Parmensis, 2023)
Metastatic urothelial bladder cancer is associated with high mortality rates. The advent of immunocheckpoint inhibitors (ICIs), with the approval of pembrolizumab in second line treatment, has changed the treatment landscape and improved clinical outcomes of patients. Until recently, subsequent lines of therapy have been limited to single-agents chemotherapy, poor efficacy and relevant toxicities. Recent studies in pretreated urothelial bladder cancer have led to the approval in clinical practice of enfortumab vedotin, demonstrating better clinical efficacy compared with the standard of care. Herein we report a case of a 57-year-old male patient with metastatic bladder cancer, who had unsatisfactory responses to first-line chemotherapy and subsequent second-line immunotherapy. Based on robust data of efficacy and safety from clinical trials, we treated the patient with enfortumab vedotin as third-line therapy. An initial adverse event, probably not strictly related to the drug, led to temporarily discontinuation of enfortumab vedotin and subsequent administration with a dose reduction. Despite this, the drug induced a first partial response on most of the metastatic sites and a complete response on lung and pelvic metastases was subsequently observed. Of note, responses were durable, with good tolerability and improvement in cancer-associated symptoms, such as pain.